2018
DOI: 10.1029/2017jf004560
|View full text |Cite
|
Sign up to set email alerts
|

On Bedload and Suspended Load Measurement Performances in Sheet Flows Using Acoustic and Conductivity Profilers

Abstract: Intense sediment transport experiments were performed in a gravity‐driven open‐channel flow with two sizes of uniformly distributed nonspherical acrylic particles having median diameters of 1.0 and 3.0 mm and a maximum packing volumetric concentration (ϕ) of 0.55. The flow conditions were adapted to each particle size to ensure similar sediment transport flow regimes as sheet flow corresponding to Shields numbers slightly above unity and a suspension number, ratio of settling velocity to friction velocity, nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 47 publications
(100 reference statements)
0
26
0
Order By: Relevance
“…In the present experiments, the ACVP technology was used for the first time under wave‐driven sheet flow conditions with real sands. This experimental condition is different from previous studies in which the ACVP has been successfully used in gravity‐current‐driven sheet flows with light‐weight particles (Fromant et al, ; Revil‐Baudard et al, , ). To assess the performance of the ACVP under these conditions, we compare ACVP‐measured erosion depth, sheet flow layer thickness, and sand transport rate with the corresponding CCM+ measurements at x = 54.5 m.…”
Section: Methodsmentioning
confidence: 75%
“…In the present experiments, the ACVP technology was used for the first time under wave‐driven sheet flow conditions with real sands. This experimental condition is different from previous studies in which the ACVP has been successfully used in gravity‐current‐driven sheet flows with light‐weight particles (Fromant et al, ; Revil‐Baudard et al, , ). To assess the performance of the ACVP under these conditions, we compare ACVP‐measured erosion depth, sheet flow layer thickness, and sand transport rate with the corresponding CCM+ measurements at x = 54.5 m.…”
Section: Methodsmentioning
confidence: 75%
“…Over recent years a novel acoustic measurement tool, the Acoustic Concentration and Velocity Profiler, ACVP, Thorne et al, 2011;Thorne and Hurther, 2014;Wilson and Hay, 2016) has been under development. Compared to previous sediment flux profilers, the ACVP technology is not restricted to suspended particle flux profiling, but extends the sediment flux profiling at turbulent flow scales into the dense bedload layer Naqshband et al, 2014b;Revil-Baudard et al, 2015Fromant et al, 2017Fromant et al, , 2018. In the present study, it is shown show how these nearbed ACVP measurement, are used complementary with the BASSI and 3D-ARP data, to investigate wave-driven sand transport processes over a rippled sand-bed.…”
Section: Introductionmentioning
confidence: 83%
“…A time series of volumetric concentration profiles, ϕ ( t , z ), from within the bed to the top of the FOBS (i.e., the 20 th sensor, z FOBS , 20 ≈ 1.92 m) was constructed for every trial (and site) by merging the instantaneous concentration profiles measured by the FOBS and CCP (Mieras et al, ). FOBS calibrations revealed signal saturation at ϕ ~ 0.05 m 3 /m 3 , whereas CCP measurements become less reliable for ϕ < 0.05 m 3 /m 3 (Fromant et al, ; Lanckriet et al, ). Therefore, when concentrations were observed by both a FOBS and a CCP at a particular elevation, where ϕ FOBS ≤ 0.05 m 3 /m 3 and ϕ CCP ≥ 0.05 m 3 /m 3 , precedence was given to CCP data.…”
Section: Data Treatmentmentioning
confidence: 99%